A high-throughput preparation method and optical performance screening method of thickness gradient chalcogenide phase change thin film
Patent Information
- Application Number
- CN202611487077.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-27
AI Technical Summary
然而,将其直接应用于硫系相变薄膜的厚度梯度制备时仍面临诸多制约
[0009]与现有技术相比,本发明的优点在于:本发明一种用于硫系相变薄膜的高通量制备方法,采用高通量磁控共溅射法,通过精准调整靶材溅射角度,在衬底静止不旋转的条件下得到成分均匀、厚度沿梯度方向连续差异分布的高通量样品库,一次沉积即可获得覆盖宽厚度范围的样品阵列;并创新性地结合薄膜干涉显色效应,利用厚度变化引起的反射颜色梯度差异实现整片样品库的可视化快速表征与筛选,将传统逐点测量升级为并行成像读出,显著提升厚度-性能匹配研究的效率与可靠性。本发明有效克服了传统硫系相变薄膜仅能单一厚度沉积、厚度与光学/相变性能匹配筛选效率低下的技术缺陷,实现了相变薄膜从制备到性能筛选的全流程高通量,消除批次间工艺误差,大幅提升研发效率,可广泛应用于相变存储器(PCRAM)、中远红外光学超表面、红外探测器、光波导等器件的研发与制造。
Smart Images

Figure CN122979849A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to semiconductor optoelectronic materials and high-throughput material preparation technology, specifically to a chalcogenide phase change thin film with controllable thickness gradient and its high-throughput magnetron sputtering preparation method, as well as a high-throughput screening method for optical properties based on colorimetry. Background Technology
[0002] Chalcogenide phase change films, with their rapid and reversible phase transition between amorphous and crystalline states and significant differences in optical and electrical properties, have become key functional materials in fields such as phase change RAM (PCRAM), rewritable optical storage, and neuromorphic computing. Film thickness is a critical parameter determining phase transition kinetics, resistivity / optical contrast, and cycle durability; therefore, systematic screening and evaluation of films of different thicknesses are necessary during device development.
[0003] However, existing chalcogenide phase change thin film preparation technologies still face significant bottlenecks in constructing thickness gradients. Traditional methods often employ single-component magnetron sputtering or electron beam evaporation, following a sequential "single sample, single deposition" model: each sample of a specific thickness requires independent completion of the entire process of vacuuming, pre-sputtering, deposition, and sampling. This model not only has a lengthy process cycle and low target utilization, but also suffers from significant comparability between samples of different thicknesses due to minute fluctuations in process conditions such as vacuum level, background pressure, and target condition between different batches, making it difficult to meet the data consistency requirements of high-throughput material screening.
[0004] In recent years, some high-throughput composite fabrication techniques have been developed, such as using mask blocking or substrate movement to achieve gradient distributions of film thickness or composition. However, their direct application to the preparation of thickness gradients in chalcogenide phase change films still faces many limitations. Mechanical masking systems are prone to introducing particulate contamination, posing a serious threat to nanoscale phase change films that are highly sensitive to defects. While composition control methods based on multi-target co-sputtering can precisely control the doping ratio, their initial design focuses on continuous adjustment of stoichiometry. There is still a lack of efficient and low-cost dedicated technical solutions for achieving large-scale, continuous, and linear thickness gradients with a single component. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide an efficient high-throughput preparation method and an optical performance screening method for preparing chalcogenide thin films of different thicknesses.
[0006] The technical solution adopted by this invention to solve the above-mentioned technical problems is as follows: a high-throughput preparation method for chalcogenide phase change films with thickness gradient, comprising the following steps: (1) The substrate was cleaned in an ultrasonic cleaner for 10 minutes in sequence with isopropanol, anhydrous ethanol and deionized water, and then dried with a nitrogen gun. After cleaning, it was dried and stored. (2) High-purity Ge2Sb2Te5 (99.99%), ITO (99.99%), and Ag (99.99%) were used as sputtering targets. The Ag target was installed at the No. 1 DC sputtering target position of the magnetron sputtering system, and the Ge2Sb2Te5 target and ITO target were installed at the No. 2 and No. 3 RF sputtering targets of the magnetron sputtering system, respectively. The sputtering tilt angle of the Ge2Sb2Te5 target was adjusted so that the target normal and the substrate normal formed a preset angle. The thickness gradient range was controlled by adjusting the angle. (3) Turn on the vacuum system to evacuate the chamber until the chamber pressure is below 3.0 × 10⁻⁶. -6 Pa; (4) Introduce 100 sccm of high-purity argon gas into the chamber to ignite it. After ignition, adjust the argon gas flow rate to 30 sccm and deposit each film layer sequentially at room temperature: turn on the Ag DC sputtering target and deposit the Ag reflective layer; turn on the ITO RF sputtering target and deposit the ITO buffer layer above the Ag reflective layer; turn on the Ge2Sb2Te5 RF sputtering target and, relying on the deposition flux gradient formed by the tilt of the target, grow a Ge2Sb2Te5 phase change functional layer with a continuously linearly varying thickness on the surface of the ITO buffer layer; turn on the ITO RF sputtering target again and deposit an ultrathin ITO protective layer to isolate the air and inhibit the oxidation failure of Ge2Sb2Te5. (5) Place the deposited sample in a vacuum annealing furnace and perform annealing treatment at different temperatures under argon protection to obtain Ge2Sb2Te5 thin films with different crystal phases.
[0007] Furthermore, the substrate is a 5-inch single-polished silicon dioxide wafer; the thickness range of the Ge2Sb2Te5 functional layer can be adjusted by the target angle and sputtering power, with a typical range of 5–70 nm; the complete film structure from bottom to top is: substrate / 300 nm Ag reflective layer / 150 nm ITO buffer layer / thickness gradient Ge2Sb2Te5 functional layer / 10 nm ITO protective layer.
[0008] This invention also provides a high-throughput screening method for the optical properties of chalcogenide phase change thin films, comprising the following steps: (1) Colorimetric data acquisition: A D65 standard light source spectrophotometer was used to collect CIE Lab colorimetric parameters at different locations along the thickness gradient direction of the sample library in 5nm steps, including lightness L*. 、 Red-green hue a*, blue-yellow hue b*; the original chromaticity data collected were filtered and denoised using a 7-point moving average method. (2) Construction of two-dimensional color mapping: Based on the chromaticity parameters corresponding to different annealing temperatures and different Ge2Sb2Te5 thicknesses, a two-dimensional color mapping map of annealing temperature-Ge2Sb2Te5 thickness is constructed, and the film thickness range is intuitively determined by the hue. (3) Optical constant test: The refractive index n and extinction coefficient k of amorphous, crystalline Ge2Sb2Te5 thin films and ITO thin films in the 350-1700 nm band were tested using an elliptic polarization spectrometer. (4) High-contrast film thickness selection: Based on measured optical constants, the total CIEDE2000 color difference ΔE of crystalline and amorphous Ge2Sb2Te5 films under different ITO protective layer thicknesses and different Ge2Sb2Te5 thicknesses was simulated and calculated. The film thickness combination corresponding to high ΔE was selected as the preferred process parameters for high optical contrast. The total color difference ΔE is the total CIEDE2000 color difference. The higher the ΔE value, the greater the color difference that can be perceived by the human eye between amorphous and crystalline Ge2Sb2Te5 films.
[0009] Compared with existing technologies, the advantages of this invention are as follows: This invention provides a high-throughput preparation method for chalcogenide phase change thin films, employing a high-throughput magnetron co-sputtering method. By precisely adjusting the target sputtering angle, a high-throughput sample library with uniform composition and continuously varying thickness along the gradient direction is obtained under the condition that the substrate is stationary and does not rotate. A sample array covering a wide thickness range can be obtained in a single deposition. Furthermore, it innovatively combines the thin film interference color rendering effect, utilizing the difference in reflected color gradient caused by thickness variations to achieve rapid and visual characterization and screening of the entire sample library. This upgrades traditional point-by-point measurement to parallel imaging readout, significantly improving the efficiency and reliability of thickness-performance matching studies. This invention effectively overcomes the technical shortcomings of traditional chalcogenide phase change thin films, which can only be deposited at a single thickness and have low efficiency in thickness-optical / phase change performance matching and screening. It achieves high-throughput throughout the entire process of phase change thin film preparation and performance screening, eliminates batch-to-batch process errors, and greatly improves R&D efficiency. It can be widely applied to the R&D and manufacturing of devices such as phase change memory (PCRAM), mid- and far-infrared optical metasurfaces, infrared detectors, and optical waveguides. Attached Figure Description
[0010] Figure 1 This is a top view of the four-target cavity layout for high-throughput magnetron sputtering of the present invention, with target number 2 being an empty target position; Figure 2 This is a schematic diagram of the cross-sectional structure and thickness distribution of the Ge2Sb2Te5 thickness gradient laminated thin film of the present invention; Figure 3 Color photographs of a high-throughput sample library of Ge2Sb2Te5 thickness gradients taken under white light at different annealing temperatures; Figure 4 The curves showing the variation of lightness L* with the thickness of Ge2Sb2Te5 at different annealing temperatures; Figure 5 The curves showing the variation of the red-green color parameter a* with the thickness of Ge2Sb2Te5 at different annealing temperatures are shown. Figure 6The curves showing the variation of the blue-yellowness parameter b* with the thickness of Ge2Sb2Te5 at different annealing temperatures are shown. Figure 7 This is a two-dimensional color mapping of Ge2Sb2Te5 thin films reconstructed based on CIE Lab chromaticity parameters; Figure 8 The spectral curves of refractive index n and extinction coefficient k of amorphous Ge2Sb2Te5, crystalline Ge2Sb2Te5 and ITO thin film are shown. Figure 9 Thermographic diagram of color difference intensity coupled with ITO protective layer thickness and Ge2Sb2Te5 film thickness. Detailed Implementation
[0011] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. I. Specific Implementation Methods This embodiment employs a four-target magnetron sputtering system with a graduated rotating support to prepare a sample library of Ge2Sb2Te5 chalcogenide phase transition thin films with gradually varying thickness gradients. The specific steps are as follows: (1) The substrate was cleaned in an ultrasonic cleaner for 10 minutes in sequence with isopropanol, anhydrous ethanol and deionized water, and then dried with a nitrogen gun. After cleaning, it was dried and stored. (2) In magnetron sputtering coating systems, such as Figure 1 As shown, a silicon dioxide wafer is used as the substrate, and steps are created on the SiO2 substrate using adhesive tape. An Ag target is mounted on the magnetron sputtering target No. 1 (DC), and Ge2Sb2Te5 and ITO targets are mounted on the magnetron sputtering targets No. 2 and No. 3 (RF). The rotating support of the Ge2Sb2Te5 target is adjusted to graduation 4, corresponding to an angle of approximately 5° between the target normal and the substrate normal. The sputtering chamber of the magnetron sputtering system is then evacuated to a vacuum level of 3.0 × 10⁻⁶. -6Pa, then high-purity argon gas with a volumetric flow rate of 100 sccm is introduced into the sputtering chamber until the gas pressure in the sputtering chamber reaches the pressure required for ignition. After ignition, the argon gas volumetric flow rate is adjusted to 30 sccm, and sputtering deposition is performed at room temperature. First, Ag DC sputtering target No. 1 is turned on, the sputtering power is set to 40W, and deposition is carried out for 20 minutes to prepare a 300nm thick Ag high-reflectivity underlayer on the SiO2 substrate. Then, ITO RF sputtering target No. 4 is turned on, the sputtering power is set to 80W, and the deposition time is 20 minutes to prepare a 150nm thick ITO buffer layer above the Ag reflective layer. Then, target No. 3 is turned on. Using a Ge2Sb2Te5 RF sputtering target with a sputtering power of 30W and a single deposition time of 3 minutes, the substrate rotation speed was set to 0. Utilizing a target tilt gradient sputtering process, a Ge2Sb2Te5 phase change functional layer with a continuously linearly varying thickness range of 5–70 nm was grown on the surface of the ITO buffer layer. Finally, ITO target #4 was used again for 2 minutes to prepare a 10 nm ultrathin ITO protective layer, which covered the surface of the Ge2Sb2Te5 film, isolating it from air and suppressing oxidation failure of the Ge2Sb2Te5 film, thus obtaining the deposited Ge2Sb2Te5 sulfide phase change film.
[0013] II. Analysis of Experimental Results The above-mentioned film properties have been tested extensively, and the results are as follows: 1. Thickness measurements were performed on each sample point in the sample library using a Veeco Dektak 150 probe-type surface profilometer. Five sets of measurements were taken at different locations, and the average value of the data was calculated. The sample thickness in this embodiment is as follows: Figure 2 As shown.
[0014] 2. Figure 3 The three long strips from top to bottom correspond to gradient Ge2Sb2Te5 films prepared at 250℃, 200℃, and room temperature (30℃), respectively. The bottom strip is a pure amorphous Ge2Sb2Te5 film deposited at room temperature. The middle strip is a sample annealed at 200℃, where the film partially crystallizes to form an FCC phase crystalline Ge2Sb2Te5. The top strip is a sample annealed at 250℃, where the film is completely crystallized into a hexagonal phase Ge2Sb2Te5. The thickness of Ge2Sb2Te5 in each sample gradually changes from 5nm to 70nm along the horizontal direction, and the interference color transitions smoothly with the thickness, intuitively demonstrating the synergistic regulatory effect of the annealed crystalline phase and film thickness on the apparent structural color of the Ge2Sb2Te5 film.
[0015] 3. Figure 4 , Figure 5 , Figure 6 The figures show the lightness (L), chromaticity (a), and chromaticity (b) of a gradient Ge₂Sb₂Te₅ thin film as a function of Ge₂Sb₂Te₅ thickness. A D65 spectrophotometer was used to measure these values. Figure 3The sample library was sampled point-by-point at 5nm intervals. Raw chromaticity data were extracted from amorphous samples at 30℃, partially FCC-crystallized samples at 200℃, and fully Hex-crystallized samples at 250℃. After noise reduction using a 7-point moving average filter, the data was plotted. The blue, red, and black curves correspond to samples at 30℃, 200℃, and 250℃, respectively. L* represents film brightness; higher annealing temperatures result in higher brightness for the same thickness, and L* decreases monotonically with increasing film thickness for all samples. a* represents red-green tendency; amorphous samples show the strongest red hue, while crystalline samples at 250℃ are generally greenish. b* represents yellow-blue tendency; higher annealing temperatures result in a more pronounced yellow hue, while thicker amorphous film regions turn bluish-purple. These three sets of chromaticity parameters collectively determine the interference colors of the thin film, providing quantitative data support for the two-dimensional color mapping cloud image.
[0016] 4. Figure 7 This is a two-dimensional mapping contour map reconstructed based on CIE Lab chromaticity parameters. The horizontal axis represents the thickness of the Ge2Sb2Te5 film (5–70 nm), and the vertical axis represents the annealing temperature (180–260 °C). Different colors in the figure intuitively reflect the thickness of the Ge2Sb2Te5 film under corresponding process conditions, while also demonstrating the synergistic regulatory effect of the annealing crystal phase. At the same annealing temperature, as the thickness of Ge2Sb2Te5 increases from 5 nm to 70 nm, the contour map hue smoothly transitions from bright yellow to reddish-purple; at the same thickness, as the annealing temperature increases, the overall color of the film shifts towards yellowish-green. This contour map visualizes the thickness variation pattern with a continuous color gradient, and the thickness range of the Ge2Sb2Te5 film can be quickly determined by hue, achieving non-contact, parallel rapid thickness screening.
[0017] 5. Optical constants of Ge₂Sb₂Te₅ and ITO thin films were measured using an elliptic polarization spectrometer. Dispersion curves of refractive index n and extinction coefficient k in the 350-1700 nm band were obtained. The test results are as follows: Figure 8 As shown.
[0018] 6. Figure 9 This is a thickness-coupled color difference thermogram of the ITO / Ge2Sb2Te5 bilayer film, obtained based on elliptic measurements of the refractive index (n) and extinction coefficient (k) of Ge2Sb2Te5 and ITO thin films, combined with simulations using the CIE Lab colorimetric system. The horizontal axis represents the thickness of the top ITO layer, the vertical axis represents the thickness of Ge2Sb2Te5, and the color scale represents the total color difference ΔE between crystalline and amorphous films. Higher ΔE values result in more significant visual distinction between the two crystalline film types. A high color difference peak exists in the Ge2Sb2Te5 thin-layer region, and ΔE decreases overall with increasing Ge2Sb2Te5 thickness, which can be used to quickly screen for film thickness matching processes with high contrast color rendering.
[0019] The foregoing description is not intended to limit the invention, nor is the invention limited to the examples given. Any changes, modifications, additions, or substitutions made by those skilled in the art within the scope of the invention should also be considered within the protection scope of the invention.
Claims
1. A high-throughput preparation method for a thickness-gradient chalcogenide phase change thin film, characterized in that, Includes the following steps: (1) Clean and dry the substrate; (2) Provide a magnetron sputtering system, install the Ag target at the DC sputtering target position, install the ITO target and the Ge2Sb2Te5 target at the RF sputtering target position respectively, and adjust the sputtering tilt angle of the Ge2Sb2Te5 target so that the target normal and the substrate normal form a preset angle; (3) Evacuate the sputtering chamber until the chamber pressure is below 3.0 × 10⁻⁶. -6 Pa; (4) High-purity argon gas is introduced into the chamber, and the argon gas flow rate is stabilized after ignition. At room temperature, an Ag reflective layer, an ITO buffer layer, a Ge2Sb2Te5 functional layer and an ITO protective layer are deposited sequentially. When depositing the Ge2Sb2Te5 functional layer, the substrate rotation speed is set to 0. The deposition flux gradient formed by the tilt of the Ge2Sb2Te5 target is used to generate a Ge2Sb2Te5 thin film with a continuously linearly varying thickness on the substrate surface in one step.
2. The high-throughput preparation method according to claim 1, characterized in that: The substrate is any one of silicon dioxide, quartz, or calcium fluoride.
3. The high-throughput preparation method according to claim 1, characterized in that: By adjusting the sputtering tilt angle or sputtering power of the Ge2Sb2Te5 target, the thickness gradient range and thickness difference of the Ge2Sb2Te5 film can be controlled.
4. The high-throughput preparation method according to claim 1, characterized in that: The thickness of the Ge2Sb2Te5 functional layer ranges from 5 to 70 nm.
5. The high-throughput preparation method according to claim 1, characterized in that: In step (4), the sputtering power of the Ag reflective layer is 40 W and the deposition thickness is 300 nm; the sputtering power of the ITO buffer layer is 80 W and the deposition thickness is 150 nm; the sputtering power of the Ge2Sb2Te5 functional layer is 30 W; and the deposition thickness of the ITO protective layer is 10 nm.
6. A method for screening the optical properties of chalcogenide phase change thin films with thickness gradients, characterized in that, A thickness gradient Ge2Sb2Te5 thin film sample library was prepared using the method described in any one of claims 1 to 5, and then screened through the following steps: (1) Colorimetric data acquisition: A D65 standard light source spectrophotometer was used to collect CIE Lab colorimetric parameters at different locations along the thickness gradient direction of the sample library, including lightness L*. 、 Red-green hue intensity a*, blue-yellow hue intensity b*; (2) Construction of two-dimensional color mapping: Based on the chromaticity parameters corresponding to different annealing temperatures and different Ge2Sb2Te5 thicknesses, a two-dimensional color mapping map of annealing temperature-Ge2Sb2Te5 thickness is constructed. (3) Optical constant test: The refractive index n and extinction coefficient k of amorphous, crystalline Ge2Sb2Te5 thin films and ITO thin films in the 350-1700 nm band were tested using an elliptic polarization spectrometer. (4) High contrast film thickness screening: Based on the measured optical constants, the total color difference ΔE of crystalline and amorphous Ge2Sb2Te5 films under different ITO protective layer thicknesses and different Ge2Sb2Te5 thicknesses is calculated by simulation. The film thickness combination corresponding to high ΔE is selected as the preferred process parameters.
7. The screening method according to claim 6, characterized in that: In step (1), the thickness step size for chromaticity data acquisition is 5 nm; the acquired raw chromaticity data is filtered and denoised using the 7-point moving average method.